Analisis Pengaruh Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR), Dan Net Interest Margin (NIM) Terhadap Profitabilitas Pada Bank Go Public Yang Terdaftar Di BEI - Adiyanto, Adiyanto; , Nur Ahmad, SE., MSi (2016)
The aims of study to analyse effect of Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Net Interest Margin (NIM) to Profitability at Bank Go Public in Indonesian Stock Exchanges (ISE) Listed. Population of study used banking in Indonesian Stock Exchanges list at 2012-2014. This study used 31 sample in the bank with Purposive Sampling. Analyse data used pooled time series with fixed effect model. The reseacrh used secondary data with Annual Report ratios with 93 observation. The result of study NPL negative effect and significant to ROA. CAR had a negative effect and significant to ROA. LDR had a negative effect and no significant to ROA. NIM had a positive effect and significant. Simultaniously NPL, CAR, LDR, and NIM had significant effect to ROA in the bank go public in Indonesian Stock Exchanges (ISE) list period 2012-2014.